Unlocking circularity: A PESTLE-SWOT analysis for sustainable black soldier fly (BSF) larvae waste valorization in an emerging economy context (Case study: Pasuruan, Indonesia) - Wahid, Abdul; Suhartini, Sri; Asmaul Mustaniroh, Siti; Nurika, Irnia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Escalating organic waste poses a global challenge, particularly in emerging economies like Indonesia. The Circular Economy (CE) framework, utilizing Black Soldier Fly (BSF) larvae for waste valorization, offers a promising sustainable solution, yet successful implementation requires understanding contextual factors. This study analyzed external (PESTLE) and internal (SWOT) factors influencing CE adoption in BSF-based organic waste management in Pasuruan Regency, Indonesia. A mixed-methods approach with surveys of 30 BSF entrepreneurs and expert consultations was employed. PESTLE analysis identified macro-environmental influences, informing the SWOT analysis. Weighted scores for SWOT factors assessed BSF enterprises' strategic positioning. Key opportunities include rising market demand for BSF products and growing partnerships. Strengths are existing cooperation networks and BSF's waste reduction efficiency. However, significant weaknesses like limited CE understanding, reliance on basic technology, and lack of supportive regulations, coupled with threats like high infrastructure costs and limited advanced processing knowledge, create challenges. Overall Internal Factors Analysis Summary/IFAS (-0.15) and External Factors Analysis Summary/EFAS (-0.53) scores indicate a defensive strategic position. Unlocking circularity for BSF waste valorization in Pasuruan necessitates addressing regulatory gaps, enhancing technical capacity and CE knowledge, and fostering multi-stakeholder collaborations. Strategic interventions in policy, finance, and technology are crucial for transitioning towards a sustainable BSF-CE model.